Tropikal / Mawar Nurdiana Binti Rosni - Rosni, Mawar Nurdiana (Collage of Creative Arts, 2022)
The younger generation will be more familiar with and aware of the origin of natural dyes that can be used to counteract the usage of synthetic dyes when exposed to them. I hope to strengthen natural dyes from mangosteen, turmeric, nonie, coconut, and butterfly pea as dye stuff for textiles. The colour variations derived from these five plants are capable of producing natural dyes of various hues and tones based on the type of mordant added. My designs are arranged in an overall style and made to give a happy and warm tropical feel to my project.